2021
DOI: 10.1016/j.jtho.2021.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoking and Risk of Second Primary Lung Cancer

Abstract: Introduction: Lung cancer survivors are at high risk of developing a second primary lung cancer (SPLC). However, SPLC risk factors have not been established and the impact of tobacco smoking remains controversial. We examined the risk factors for SPLC across multiple epidemiologic cohorts and evaluated the impact of smoking cessation on reducing SPLC risk.Methods: We analyzed data from 7059 participants in the Multiethnic Cohort (MEC) diagnosed with an initial primary lung cancer (IPLC) between 1993 and 2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 34 publications
2
51
0
Order By: Relevance
“…In evaluating the association between survival and SPLC, we considered SPLC diagnosis as a time-varying predictor to account for patients whose SPLC status changed from a single primary lung cancer to SPLC during the study period. The model was adjusted for known prognostic factors and risk factors for SPLC based on prior literature ( 8-10 , 13 , 17 ): sex, race, age at IPLC diagnosis, IPLC stage, and IPLC histology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In evaluating the association between survival and SPLC, we considered SPLC diagnosis as a time-varying predictor to account for patients whose SPLC status changed from a single primary lung cancer to SPLC during the study period. The model was adjusted for known prognostic factors and risk factors for SPLC based on prior literature ( 8-10 , 13 , 17 ): sex, race, age at IPLC diagnosis, IPLC stage, and IPLC histology.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have examined potential risk factors and predictive models for SPLC in an effort to establish efficient screening strategies for SPLC ( 8-12 ). Radiotherapy for initial primary lung cancer (IPLC) is associated with an increased risk of SPLC ( 11 ), and smoking is a statistically significant risk factor for SPLC based on an international multicohort study ( 8 ). Prediction models for SPLC risk have been developed to identify high-risk lung cancer survivors for surveillance and screening for SPLC ( 9 , 12 , 13 ).…”
mentioning
confidence: 99%
“…Furthermore, MEC helped increase the power of the study as a primary cohort by providing the largest number of SPLC cases with long-term follow-up and detailed exposure data among all cohorts considered. We used a binary IPLC staging variable in predicting SPLC risk, merging patients with stage IA to IIIA IPLCs into an early-stage IPLC group based on the literature ( 17 , 35 ); also, analyses using SEER showed that SPLC risk does not vary statistically significantly across stage IA to IIIA IPLCs (data not shown). Therefore, the clinical utility of the proposed model would not be diminished given that the model continues to capture well the SPLC risk variations using parsimonious dichotomous staging parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer, which accounts for 11.6% of all newly diagnosed cancer cases and 18.4% of cancer-related deaths [1], brings a growing global burden of disease. Smoking has been identified as the most common risk factor for lung cancer, and a large number of epidemiological researches support this connection [2][3][4]. Smoking cessation before middle age can effectively decrease lung cancer risk.…”
Section: Introductionmentioning
confidence: 98%